Late hematogenous seeding and infection of a femoropopliteal Omniflow II bypass. (October 2021) - Mufty, Hozan; Houthoofd, Sabrina; Daenens, Kim; Fourneau, Inge
Introduction: Omniflow II is promoted as an infection-resistant vascular graft. It is used to treat vascular graft infection; nevertheless, early graft infection has been reported. Report: A 71-year-old patient was treated with an Omniflow II bypass for a non-healing diabetic foot ulcer. Seven months postoperatively, late infection occurred secondary to hematogenous spread from a persistent foot infection. Conclusion: We report on the first case of late infection of an Omniflow II vascular graft caused by hematogenous spread. Despite promising results of the Omniflow II graft in the treatment of vascular graft infection, late infection may not be avoided.